TYPES AND CRITERIA OF ASSESSING SPEAKING SKILL - Sh.T.Urakova; Jumayeva Muhayyo Hasan qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract:Assessing speaking skills is an important aspect of foreign language learning. This article examines the different types and criteria for assessing speaking skills.Firstly, the types of assessment are discussed, including diagnostic, formative, and summative assessment. Secondly, the key criteria for assessing speaking skills are analyzed, such as fluency, accuracy, complexity, and interactivity. This article emphasizes the importance of a comprehensive approach to speaking assessment, considering various types and criteria to provide a thorough analysis of learners' language abilities.